2016
DOI: 10.1002/jcb.25582
|View full text |Cite
|
Sign up to set email alerts
|

Growth Arrest‐Specific 6 (GAS6) Promotes Prostate Cancer Survival by G1 Arrest/S Phase Delay and Inhibition of Apoptosis During Chemotherapy in Bone Marrow

Abstract: Prostate cancer (PCa) is known to develop resistance to chemotherapy. Growth arrest-specific 6 (GAS6), plays a role in tumor progression by regulating growth in many cancers. Here, we explored how GAS6 regulates the cell cycle and apoptosis of PCa cells in response to chemotherapy. We found that GAS6 is sufficient to significantly increase the number and duration of G1 phase in PCa cells. Importantly, GAS6 further increased the number of G1 arrested cells during docetaxel chemotherapy. GAS6 altered the signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Co-culture of PCa cells with GAS6 +/+ OBs reduced the proportion of proliferating PCa cells compared to PCa co-cultured with GAS6 −/− OBs (Figure 5C), which is consistent with previous reports and induction of PCa dormant states (30). Co-culture of PCa cells with GAS6 +/+ OBs also revealed a 1.9 fold increase in Ki67 positive PCa cells when cultured with NE compared to vehicle controls as determined by flow cytometry (Figure 5C).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Co-culture of PCa cells with GAS6 +/+ OBs reduced the proportion of proliferating PCa cells compared to PCa co-cultured with GAS6 −/− OBs (Figure 5C), which is consistent with previous reports and induction of PCa dormant states (30). Co-culture of PCa cells with GAS6 +/+ OBs also revealed a 1.9 fold increase in Ki67 positive PCa cells when cultured with NE compared to vehicle controls as determined by flow cytometry (Figure 5C).…”
Section: Resultssupporting
confidence: 92%
“…Previously we have observed that GAS6 expression by osteoblasts regulates PCa dormancy through interactions with MERTK (8,29,30,33). First, we sought to confirm the GAS6 mRNA results at the protein level.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…There is also evidence that GAS6 increases the number of prostate cancer cells with a stem cell phenotype, which is CD133 positive/CD44 positive, within the bone marrow [103]. Cancer stem cells (CSCs) are proposed to be stem like cells found in tumors and possess the capability to self-renew and differentiate into new diverse tumor cells.…”
Section: Cancer Cell Implantation and Survivalmentioning
confidence: 99%